Phospholes: Molecular Engineering of "Click"‐Phospholes Towards Self‐Assembled Luminescent Soft Materials (Adv. Funct. Mater. 7/2014). (February 2014) - He, Xiaoming; Lin, Jian‐Bin; Kan, Wang Hay; Dong, Pengcheng; Trudel, Simon; Baumgartner, Thomas
<x xml:space="preserve">Abstract</x> T. Baumgartner and co‐workers report the design of organophosphorus‐based soft materials on page 897. The self‐assembly of these materials can be engineered on the molecular level using simple phosphorus‐chemical approaches, giving rise to organogels and liquid crystals. The cover image shows the polarized optical micrograph of a dried gel exhibiting highly ordered layered features that reflect the supramolecular organization of a single‐crystalline model compound. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>